2014
DOI: 10.5539/enrr.v4n3p103
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of canopy interception and transpiration of openly-grown eastern redcedar in central Okalhoma

Abstract: Eastern redcedar (Juniperus virginiana L.) is rapidly encroaching and degrading native prairie and rangeland landscapes in the Great Plains of the U.S. Little is known concerning the impacts of increasing redcedar density and areal coverage on local and regional water budgets through transpiration (T r ) and canopy interception (C I ) of precipitation. Limited T r and C I studies have been conducted in dense stands of redcedar but results from these studies may not be applicable to redcedar growing in open env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…However, recent studies emphasized differences in both ecophysiological characteristics and soil physical and hydrological properties associated with woody encroachment compared to forests. Although juniper trees are usually shorter than pine trees, the canopy interception of juniper can be 2-3 mm higher than any other species in the region including the oak trees (Owens et al, 2006;Starks et al, 2014). The stomatal conductance was set at 0.001-0.002 m/s based on field measurement by Will et al (unpublished data), which is lower than pine trees that are typically 0.002 m/s.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies emphasized differences in both ecophysiological characteristics and soil physical and hydrological properties associated with woody encroachment compared to forests. Although juniper trees are usually shorter than pine trees, the canopy interception of juniper can be 2-3 mm higher than any other species in the region including the oak trees (Owens et al, 2006;Starks et al, 2014). The stomatal conductance was set at 0.001-0.002 m/s based on field measurement by Will et al (unpublished data), which is lower than pine trees that are typically 0.002 m/s.…”
Section: Discussionmentioning
confidence: 99%
“…Starks et al (2014) showed that redcedar maximum canopy storage (CANMAX) was about 2.4 mm in an open environment. Our measurements showed a range of 2.14-3.44 depending on stage of canopy closure (manuscript in review).…”
Section: Swat Model Description and Eastern Redcedar Parameterizationmentioning
confidence: 98%
See 1 more Smart Citation
“…Canopy and litter interception affect local recharge of groundwater by modifying the net precipitation and thus the net water input to the soil. Studies on interception loss to woody plants include [32,109,[118][119][120][121], among others. One such study found that woody plants have higher canopy storage capacity for rainfall compared to grassland [109].…”
Section: Canopy and Litter Interceptionmentioning
confidence: 99%
“…This trend has accelerated in recent decades (Wilcox 2010, Twidwell et al 2013) modifying and in some cases threatening key ecosystem services (Norris et al 2001, Throop et al 2012, including biodiversity (Pierce and Reich 2010), species distribution and composition (Dobson et al 1997, Chapin et al 1998, Norris et al 2007, ecosystem NPP (Wilcox 2010), herbaceous (Ganguli et al 2008) and livestock production (Throop et al 2012), nutrient cycling (Archer 2010, Pierce andReich 2010), and system ecohydrology (Eggemeyer et al 2009, Awada et al 2013. There is much to be learned about the implications of shifts from open grasslands and savannas to closed-canopy woodlands on water and biogeochemical cycles (Wilcox 2010, Starks et al 2014, and the feedback of these cycle and resource availability changes on plant ecophysiological performance. Furthermore, investigating the seasonal and spatial physiological activity are necessary for modeling efforts including the estimation and forecasting of energy, water and carbon exchange, as well as NPP of a plant community and its projected dynamics in the face of climate variability and change (Hamada et al 2016).…”
Section: Introductionmentioning
confidence: 99%